AN APPLICATION OF IRIDM IN THE DECISION MAKING PROCESS ON FUEL CONVERSION OF THE MARIA REACTOR - Borysiewicz, Mieczysław Józef; Kowal, Karol; Prusiński, Piotr Andrzej; Dąbrowski, Marcin (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
Poland, when acceded to GTRI (Global Threat Reduction Initiative) in 2004, has committed to convert the nuclear fuel of the Research Reactor MARIA, operated by the National Centre for Nuclear Research (NCBJ) in Świerk. The conversion means giving up of high enriched uranium fuel containing 36% of U-235, which was used so far, and replacing it with the low enriched uranium fuel (19.7% U-235). This article describes the potential usability of the Integrated Risk Informed Decision Making (IRIDM) methodology in optimization of the fuel conversion procedure.